Leaf micromorphology and anatomy in the tribe Aristideae (Poaceae) in Iran and its systematic implications - Maasoumi, Zahra; Pakravan, Maneezheh; Hamzee, Behnam; Zarei, Roghaieh (Phytotaxa, 2023)
The present study investigated the leaf anatomy of 12 species belonging to the genera Aristida and Stipagrostis of the Aristideae tribe in Iran. Scanning electron microscopy (SEM) and light microscopy (LM) were used to observe the epidermal characteristics and transverse sections of the leaves to assess taxonomic applications of these traits. The main distinguishing traits of the species included: the presence of prickles, macrohairs and microhairs, papillae and type of wax, adaxial ribs, number of bulliform cells, number of sclerenchymatous layers and shape of silica bodies. When constructing the phenogram of Aristideae using WARD’s method and based on the 7 qualitative and 18 quantitative anatomical traits showed four taxonomic-anatomic clades with a cophenetic correlation coefficient of 1.75. Kranz anatomy in S. raddiana differed from the one seen inS. paradisea. The presence of papillae and lack of macrohairs on the leaf epidermis in S. karelinii distinguished it from S. pennata. By present findings the placement of A. coerulescens as a variety of A. adscensionis has not been ascertained. An identification key is providedbased on anatomical traits.The anatomical features of the leaves were proved to be useful for species delimitation and as a supplementary tool for identifying taxa and macromorphological traits.